Rikers Island: The Failure of a "Model" Penitentiary. (December 2020) - Mooney, Jayne; Shanahan, Jarrod
New York City's Rikers jail complex is gripped by a crisis of legitimacy. Following a series of investigations, it has been denounced as a major symbol of criminal justice dysfunction, with calls for its closure and replacement with new smaller "state of the art" jails. Yet, when it opened, Rikers was hailed as a "model" facility, at the cutting edge of prison design and prisoner rehabilitation. To elucidate the present situation, we provide a focus on the under-explored history of New York City's penal institutions.